Delving into Language and Culture into Religious Values Through Video: Sociolinguistic Analysis of the "Maccera Manurung" Tradition in the Villages of Pasang, Maiwa, Enrekang - Arsita, Amelia; Fiddienika, Arief (Dinamika Bahasa dan Budaya, 2024)
This research examines the interaction of the Maccera Manurung tradition in Pasang Village, Maiwa Enrekang District with Islamic education using a qualitative approach and case study methodology. The main focus of this research is to understand the meaning, customs and context that local communities give to this tradition, as well as its interaction with Islamic teachings. The research results show that the Maccera Manurung tradition has undergone evolution since the arrival of Islam, where people began to integrate Islamic values ​​into their traditional practices, such as appropriate behavior towards animals, harvest parties as a form of gratitude, and morals. lessons that are in line with Islamic teachings. This research also found that this tradition plays a role in strengthening adherence to Islamic principles, showing how integration between custom and religion can take place in harmony. The implications of this research for understanding Islamic education and cultural syncretization offer new insights into how local traditions and religion can influence and support each other in the context of the Pasang community. Keywords: Maccera Manurung, Islamic traditions, Cultural integration, Pasang village